Arcuate nucleus of the hypothalamus contributes to the hypophagic effect and plasma metabolic changes induced by vasoactive intestinal peptide and pituitary adenylate cyclase-activating polypeptide. (May 2022) - Martins, Andressa Busetti; Brownlow, Milene Lara; Araújo, Bruno Blanco; Garnica-Siqueira, Marcela Cristina; Zaia, Dimas Augusto Morozin; Leite, Cristiane Mota; Zaia, Cássia Thaïs Bussamra Vieira; Uchoa, Ernane Torres
Abstract: The arcuate nucleus of hypothalamus (ARC) integrates circulating factors that signal energy status. The vasoactive intestinal peptide (VIP) and pituitary adenylate cyclase-activating polypeptide (PACAP) are widely distributed in the periphery and central nervous systems (CNS) and play important roles on energy balance. The present study aimed to investigate the responses of microinjection of VIP and PACAP in the ARC on metabolic changes and food intake. In addition, the activity of neurons in the ARC following intracerebroventricular (ICV) microinjection of these peptides was also evaluated. Microinjection of VIP or PACAP in the ARC decreased fasting-induced hyperphagia and food intake, decreased total lipids, and increased free fatty acids plasma concentrations. VIP microinjection in the ARC induced hyperglycemia and decreased total cholesterol level; and PACAP reduced triglycerides concentration. ICV microinjection of VIP and PACAP enhanced neuronal activation in the ARC, associated with lower fasting-induced hyperphagia and plasma metabolic changes (only VIP). These results suggest that VIP and PACAP play important roles in ARC, inducing hypophagia and peripheral metabolic changes, as hyperglycemia, increased free fatty acids and decreased total lipids plasma levels. Graphical abstract: Schematic diagram demonstrating that VIP and PACAP act in the arcuate nucleus of hypothalamus (ARC) and induce hypophagia and plasma metabolic changes, such as increase in glucose and free fatty acids plasma levels, as well as reduction in triglycerides, total cholesterol and lipids. Image 1 Highlights: VIP or PACAP microinjection in the ARC increases free fatty acids and decreases lipids levels. ARC or ICV microinjection of VIP or PACAP reduces fasting-induced hyperphagia. Microinjection of VIP or PACAP in the ARC reduces food intake. ICV microinjection of VIP or PACAP increases activation of ARC neurons. ICV VIP increases glycemia and corticosterone and decreases free fatty acids.